METHOD FOR THE DETERMINATION OF PHYSIOLOGICALLY ACTIVE SUBSTANCES CONTAINED IN THE AMMOPHOS - Ibrohimjon Abidov (Research Focus International Scientific Journal, 2024)
The article presents the results of the development of methods for the spectrophotometric and gas chromatographic determination of benzimidazolones introduced into the composition of ammophos. The developed methods make it possible to quantitatively and qualitatively determine the content of benzimidazolone compounds.